2004-2024: 20 Years of Being Nourished in/with/through Art Education - Lee, Nicole (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
In this short reflection, I share vignettes about interactions with arts educators who have lifted me up, magnified my understanding, sparked my curiosity, broadened my capacity, supported my vision, opened doors, illuminated pathways, and encouraged me to keep going. Evident in each of these experiences is how art education can enrich one’s inner world, propelling a re-envisioning of the self and who one can become. These experiences have shaped my values and become the source material of my scholarly and professional publications over the years.